AN EVALUATION OF THE ICDS FOOD FORTIFICATION IN UTTARAKHAND - Yadav, R J; Pandey, A; Singh, P (Indian Journal of Community Health, 2012)
Objective: To assess the impact of consuming fortified blended food on the reduction of anemia and vitamin A deficiency in the beneficiary children 12-59 months, under the routine ‘programmatic conditions’ of ICDS implementation. Study Design: End line evaluation study with Probability Proportion to population Size (PPS) Sampling. Setting: Study covered 30 villages from each of two blocks of uttarakhand state. Subjects: 750 pre school children (0-6 years) were studied. Method: Thirty villages were selected by Probability Proportion to population Size (PPS), from each of the two blocks (intervention and control). From each selected village, 25 children were selected for the anthropometric measurement and dietary intake and of these, 10 children were selected for clinical and bio-chemical examination. Results: Severe anemia in the intervention block reduced significantly by 6% (from 6.1% to 0%), while in control block, the % reduction in severe anemia was 3.6% (from 3.6% to 0%). Significantly improved vitamin A status of child beneficiaries in the intervention block Kalsi is further substantiated by the significant decline in the presence of Bitot’s Spot (clinical manifestation of vitamin A deficiency in children), from 1.3% at the baseline to 0.3% at the end line. Prevalence of severe and moderate malnutrition declined significantly within both interventions as well as control blocks. Conclusion: The results of the present study state that consumption of fortified blended food by the programme beneficiaries has made a positive impact on the status of micronutrient malnutrition.